2014
DOI: 10.1186/1471-2369-15-100
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vasopressin antagonism on renal handling of sodium and water and central and brachial blood pressure during inhibition of the nitric oxide system in healthy subjects

Abstract: BackgroundTolvaptan is a selective vasopressin receptor antagonist (V2R) that increases free water excretion. We wanted to test the hypotheses that tolvaptan changes both renal handling of water and sodium and systemic hemodynamics during basal conditions and during nitric oxide (NO)-inhibition with L-NG-monomethyl-arginine (L-NMMA).MethodsNineteen healthy subjects were enrolled in a randomized, placebo-controlled, double-blind, crossover study of two examination days. Tolvaptan 15 mg or placebo was given in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
31
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(41 citation statements)
references
References 36 publications
8
31
2
Order By: Relevance
“…Surprisingly, u-AQP2 did not change after oral administration of tolvaptan, not even in response to the highest dose of tolvaptan. We measured a similar response in our previous study of tolvaptan 15 mg [12]. Most likely, this could be explained by the measured 3-fold increase in plasma AVP.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Surprisingly, u-AQP2 did not change after oral administration of tolvaptan, not even in response to the highest dose of tolvaptan. We measured a similar response in our previous study of tolvaptan 15 mg [12]. Most likely, this could be explained by the measured 3-fold increase in plasma AVP.…”
Section: Discussionsupporting
confidence: 76%
“…The present study is a continuation and expansion of a previous randomized, double-blinded, placebo-controlled crossover, single-dose study conducted by our laboratory [12]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NO is synthesized from L-arginine, a NO synthase-catalyzed process competitively inhibited by L-NMMA [ 13 ]. Previous clinical studies conducted by our laboratory demonstrated that NO promoted natriuresis and diuresis in healthy subject [ 15 , 16 ]. Although these results support that NO is involved in the V2R response in the tubular function, it is unknown whether the response is similar in ADPKD patients.…”
Section: Introductionmentioning
confidence: 99%